THE CONVERTION OF INTANGIBLE CULTURAL HERITAGE ELEMENTS TO INNOVATIVE TOURISM PRODUCTS: A CASE STUDY - Samet ÇEVİK (Fırat University, 2019)
Tourism establishments turn to innovative products and services to survive in the fierce competition environment to gain competitive advantage and to be different. As establishments' including intangible cultural heritage in their innovative products can provide of establishments to obtain various attainments at the heart of innovation, it can also be created awareness about intangible cultural heritage. In this regard the study was formed in the axis of being converted from the traditional products in the list of intangible cultural heritage to tourism products through innovative ideas. Therefore, the case study design which is one of the qualitative research methods is used in the study. "Turkish Coffee Trail Tour" which Turkish coffee culture and tradition is being converted into tourism product for the first time by Antonina Tourism Travel Agency which operates in İstanbul is chosed as case study. The datas about emergence and the content of the tour and the attainments of the tour are gathered through interview technique. The findings obtained from the study show that while this innovative product contributes to the establishment in issues like competitive advantage, image, motivation and creating loyal customer more than financial issues, it also contributes the protection and sustainability of Turkish Coffee culture and tradition.